Development corporations in the Canadian north – examples for economic grassroots initiatives among the Inuit - Fugmann, Gerlis (ERDKUNDE, 2009)
Starting with the James Bay and Northern Québec Agreement of 1975 until the Nunavik Inuit Land Claim Agreement of 2006, the Inuit in Canada have negotiated some of the most extensive land claim agreements found in the Arctic region, opening up a variety of development opportunities for the beneficiaries of these “regional agreements”. One of the central purposes of these modern land claim agreements is to create an economic base and to promote economic self-reliance for the Inuit beneficiaries. As part of a local grassroots economic development movement that can be witnessed in these regions, development corporation were created starting in the 1970s with the mandate to invest capital into businesses and economic projects to create jobs and income for the local Inuit population. This paper will look at the efforts of two particular development corporations: the Makivik Corporation in Nunavik (Northern Québec) and the Labrador Inuit Development Corporation (LIDC) in Nunatsiavut (Northern Labrador).